Selected Social Aspects of the Quality of Life: A Case of the City of Pilsen, Czech Republic - Matušková, Alena; Rousová, Magdalena (Journal for Geography, 2012)
The article deals with the development of the labour market in the city of Pilsen after 1989, which was significantly influenced by the transformation of the local industry. Apart from the traditional indicators of the labour market, the authors also deal with the proportion of foreign workers. Over the past decade, a dramatic growth of foreigners has been depicted, which was caused by the arrival of foreign investors in Pilsen as these have created a number of job opportunities for less qualified workers. The aim of the contribution is to identify both positive and negative social aspects of life in Pilsen as these are influenced by the development of the situation on the labour market in the city and also to monitor the internal and external factors influencing the development.